Identifikasi Keselamatan dan Kesehatan Kerja Pada Rumah Pemotongan Ayam Dengan Metode Job Safety Analysis di PT XYZ - Titah Amalia, Sabila; Fatimah, Fatimah (Politeknik Negeri Ketapang, 2024)
PT XYZ is one of the companies engaged in slaughtering poultry, especially chickens according to Indonesian national standards (SNI). Identification of problems in the chicken slaughtering production area process aims to control the risks and dangerous factors that occur so as to ensure occupational health and safety (OHS) of employees at PT XYZ. The analysis technique used is the Job Safety Analysis (JSA) method which consists of determining the type of work, identifying hazards and the impacts they cause, and how to control hazards. Controls carried out in general at the chicken processing stage include wearing personal protective equipment (PPE) when carrying out work, complying with existing SOPs and providing training to workers in the field they work in.